Validity and Reliability of Summative Test Assessment for Bachelor of Technology and Livelihood Education Students - Moralia, Mary Jane A.; Namoco, Sarah O. (Technium Social Sciences Journal, 2025)
Assessment is at the core of the learning process as it enables educators to determine whether learning has truly occurred. One of the essential types of evaluation is the summative assessment, which measures learners’ achievements at the end of a course and evaluates their readiness for future academic tasks or professional responsibilities. To ensure fairness and accuracy, summative tests must be both valid and reliable. This study aimed to develop a valid and reliable teacher-made summative test in Curriculum Development and Evaluation, with an Emphasis on the TM2 course, which was administered to 41 BTLEd third-year students. The quality of the test was examined using content validity, reliability, and item analysis, including difficulty and discrimination indices. A Table of Specifications (TOS) was carefully developed based on the course syllabus to guide test item construction, aligning test items with the course’s intended learning outcomes, topics, instructional hours, and cognitive levels outlined by Bloom’s Taxonomy. Content validity was confirmed through rigorous review by two course experts. Reliability was assessed using the Kuder-Richardson Formula 20 (KR-20), which yielded a coefficient of 0.94, indicating very high internal consistency. Item analysis revealed that most test items had moderate Difficulty and strong discrimination indices. From the initial 160 items, 38 were discarded, resulting in a final 80-item instrument that met established psychometric standards. This study offers a structured process for ensuring the validity and reliability of summative tests, thereby supporting high-quality assessments in teacher education.